THE DEVELOPMENT OF PHYSICAL ACTIVITY PROTOCOL IN PATIENTS WITH CONGESTIVE HEART FAILURE IN THE HOSPITAL INPATIENT WARDS - Susyanti, Deni; Suza, Dewi Elizadiani; Ariani, Yesi (Belitung Nursing Journal, 2018)
Background: Patients with congestive heart failure need a comprehensive rehabilitative program to restore post-attack physical ability and prevent re-attacks, therefore, it is necessary to develop physical activity protocols for these patients. Objective: This study aims to develop physical activity protocols for patients with congestive heart failure in the inpatient wards of the Level II Putri Hijau Hospital, Indonesia. Methods: This was an action research with 3 cycles consisting of four stages, namely: (1) reconnaissance, (2) planning, (3) action and observation, and (4) reflection. Data were collected quantitatively and qualitatively. Qualitative data were collected using in-depth interview, focus group discussion, and self-report, while quantitative data were collected using nursing knowledge questionnaire to 35 nurses selected using total sampling, and self-efficacy questionnaire about physical activity exercise to 9 patients with congestive heart failure selected using accidental sampling. Qualitative data were analyzed using content analysis, while quantitative data using descriptive statistical test. Results: Findings showed the completed compilation of physical activity protocols for patients with congestive heart failure. The results of observation showed a decrease in blood pressure of patients with congestive heart failure on the average of 3.12 mmHg after given physical activity protocol by nurses. Conclusion: The physical activity protocols for patients with congestive heart failure have been developed, and it has an impact on the increase of nurses' knowledge concerning physical activity exercise for CHF patients as well as the improvement of patients' self-efficacy or self-confidence in doing the physical activities.